Enhanced Thermoelectric Properties of Double-Filled CoSb3 via High-Pressure Regulating - Wang, Libin; Deng, Le; Qin, Jieming; Jia, Xiaopeng (Inorganic chemistry, 2018)
It has been discussed for a long time that synthetic pressure can effectively optimize thermoelectric properties. The beneficial effect of synthesis pressures on thermoelectric properties has been discussed for a long time. In this paper, it is theoretically and experimentally demonstrated that appropriate synthesis pressures can increase the figure of merit (ZT) through optimizing thermal transport and electronic transport properties. Indium and barium atoms double-filled CoSb3 samples were prepared use high-pressure and high-temperature technique for half an hour. X-ray diffraction and some structure analysis were used to reveal the relationship between microstructures and thermoelectric properties. In0.15Ba0.35Co4Sb12 samples were synthesized by different pressures; sample synthesized by 3 GPa has the best electrical transport properties, and sample synthesized by 2.5 GPa has the lowest thermal conductivity. The maximum ZT value of sample synthesized by 3.0 GPa reached 1.18.